2021
DOI: 10.1021/acsabm.1c00932
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Phospholipid Nanobiomaterials for Biomedical Applications to Lab-on-a-Chip, Drug Delivery, and Cellular Engineering

Abstract: The design of advanced nanobiomaterials to improve analytical accuracy and therapeutic efficacy has become an important prerequisite for the development of innovative nanomedicines. Recently, phospholipid nanobiomaterials including 2-methacryloyloxyethyl phosphorylcholine (MPC) have attracted great attention with remarkable characteristics such as resistance to nonspecific protein adsorption and cell adhesion for various biomedical applications. Despite many recent reports, there is a lack of comprehensive rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 181 publications
0
6
0
Order By: Relevance
“…However, cervical cancer is still a leading cause of death among women and new therapeutic strategies should be designed for its treatment . Nanotechnological approaches including the use of microfluidic devices, high-gravity techniques, microporous smart nanostructures, green methodologies, and combinations would be a great help in order to improve the efficiency, reduce the cost of methods, increase the greenness factors, and also reduce the time of drug/method discovery. …”
Section: Introductionmentioning
confidence: 99%
“…However, cervical cancer is still a leading cause of death among women and new therapeutic strategies should be designed for its treatment . Nanotechnological approaches including the use of microfluidic devices, high-gravity techniques, microporous smart nanostructures, green methodologies, and combinations would be a great help in order to improve the efficiency, reduce the cost of methods, increase the greenness factors, and also reduce the time of drug/method discovery. …”
Section: Introductionmentioning
confidence: 99%
“…The results of TEM analysis revealed that dopamine–dendrimer has a quasi-spherical structure (Figure C). However, while the TEM results are the most reliable data regarding the nanoscale morphology and size, the images suffered from low solubility and dispersibility of the nanoparticles. The examination of the size distribution of this image indicates that the particle size is in the range of 15–50 nm at about 35.917 ± 0.76 nm (Figure D). In agreement with other studies, there is a difference between TEM sizes and DLS measurements that are normally attributed to the fundamental difference between intensity- and number-weighted particle size distributions and the differences between the dry and hydrodynamic radii of particles.…”
Section: Resultsmentioning
confidence: 99%
“…Different biomaterials and their combinations are currently under investigation for tissue engineering. 42 Decellularized tissues have been widely used as either cell seeding or cell‐free substrates. 27 Extracellular matrix‐derived materials are beneficial since they provide a native microenvironment for the specific cells to survive, proliferate, and differentiate.…”
Section: Cardiac Tissue Regenerationmentioning
confidence: 99%
“…Different biomaterials and their combinations are currently under investigation for tissue engineering 42 . Decellularized tissues have been widely used as either cell seeding or cell‐free substrates 27 .…”
Section: Cardiac Tissue Regenerationmentioning
confidence: 99%